Managing stakeholder relations, natural resources and tourism: A case study from Ololosokwan, Tanzania. (January 2017) - Burgoyne, Chris; Mearns, Kevin
This manuscript investigates the complexities and challenges in the management of the Ololosokwan community conservation area in Northern Tanzania. The conservation area is adjacent to the Serengeti National Park, just south of the Tanzanian-Kenyan Border where nomadic Maasai Pastoralists are free to cross international borders in search of grazing for their cattle. The Ololosokwan community is faced with the difficulties of managing a number of conflicting land-uses and community aspirations while striving toward the maintenance of a successful and sustainable community conservation area in collaboration with a private tourism operation. Benefit sharing was found to be an effective way in which to heal negative stakeholder engagements of the past, and active participation in the development of community livelihoods was found to be a more meaningful pursuit in this cause than merely sharing money. Despite opportunities for stakeholders to show that they are willing to work together, existing conflict is likely to continue as stakeholders still mistrust each other and often align themselves with groups that share common interests.